Effectiveness of Cooperation Between MEC Institutions with Internal and External Institutions in Establishing Duafa Training Participants - Agus Setyawanto; Sudja'i Sudja'i; Bachtiar Hariyadi (EDUTEC : Journal of Education And Technology, 2022)
The study aims to find out the existing condition of the effectiveness of the MEC Education and Training program collaboration in collaboration with internal and external institutions in enabling the orphans of the education and training participants to obtain job opportunities; and The condition of the ongoing process of the MEC Education and Training collaboration program in the independence of the orphans of the training participants; 3) The condition of independence of the orphans after participating in the Yatim Mandiri MEC Education and Training program with internal and external institutions in obtaining job opportunities. This research is qualitative field research with a descriptive approach through a before - after analysis of program participants. The research object that will be developed in this research is the effectiveness of the MEC Education and Training program collaboration with internal and external institutions in enabling the underprivileged team of training participants to get job opportunities. The results of this study conclude, that the overall assessment of indicators from various assessment categories is on: 1) the existing condition of the MEC Education and Training program collaboration with internal and external institutions in making the orphans of the education and training participants get job opportunities; 2) The condition of the ongoing process of the MEC Education and Training collaboration program in establishing the poor team of training participants; 3) The condition of independence of the orphans after participating in the Yatim Mandiri MEC Education and Training program with internal and external institutions in obtaining job opportunities; shows a positive assessment close to the "good" category or shows "effective" results. This means that the MEC education and training collaboration with internal and external institutions for poor orphans has shown "effective" results in obtaining job opportunities.